Analisa Kinerja Mikrotik RB 3011 UiAS-RM dan RB 450 Gx4 pada Unmaned Aerial Vehicle - Aliyulhaq, Mohammad; Ubaidillah, Achmad; Ningrum, Eliya Kristina (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2021)
With UAV (Unmaned Aerial Vehicle) technology, surveillance functions that are usually carried out by humans are simply replaced with cameras mounted on the UAV. The results can be seen on the display control station on the GCS (Ground Control Station) system. To transmit data from the drone to the GCS, a good wireless network is required. To get a good wireless network, it is necessary to choose the right device. One of the important devices used in a network is a router. So knowledge about router performance is needed in order to determine a good router to be used on UAV and on GCS. The router that was tested for its performance in this study was the RB 3011 UiAS-RM with RB 450 Gx4. The tests were carried out using the no-load and with-load bandwidth testing methods using the traffic generator feature. From the test results, it can be concluded that the RB 3011 UiAS-RM and 450 Gx4 routers have performance that is not much different. This can be seen from the results of the no-load bandwidth test. The RB 3011 UiAS-RM router has a better uplink than the RB 450 Gx4. While the RB 450 Gx4 router has a better downlink than the RB 3011 UiAS-RM. However, when viewed from the load in the test, the RB 3011 UiAS-RM is better (CPU Load=52%) than the RB 450 Gx4 (CPU Load=25%).